Thermo-responsive self-healable hydrogels with extremely mild base degradability and bio-compatibility. (4th July 2018) - An, Heng; Xu, Kaiyue; Chang, Limin; Wang, Yong; Qin, Jianglei; Li, Wenjuan
Abstract: To face the increasing demands of self-healing hydrogels with biocompatibility and mild condition degradability, one brand new type of P(NIPAM-FPA-DMA) copolymers were prepared in this study. The copolymers were cross-linked by dihydrazide compound to form acylhydrazone containing self-healable hydrogels without additional catalysis. Herein, the chemical structure, as well as microscopic morphologies, mechanical and self-healing performances of the hydrogels were investigated. The hydrogels showed reversible thermo-responsiveness based on PNIPAM backbone and the phase transition temperature was regulated to body temperature by copolymerization of DMA. Moreover, the hydrogels could be degraded by extremely mild base of NaHCO3 based on phenolic ester bond and showed reversible gel-sol-gel transition under a variety of triggers. The in vitro toxicity experiment showed the self-healable hydrogels have good bio-compatibility. The doxorubicin-loaded hydrogels were prepared and showed controlled release profile. Altogether, these results identified the potential applications of the thermo-responsive self-healable hydrogels in bioscience and biotechnology with bio-safety. Graphical abstract: Image 1 Highlights: P(NIPAM-FPA-DMA) copolymers are synthesized and used to prepare self-healable hydrogels with acylhydrazone bond. The hydrogels showed reversible thermo-responsiveness and the phase transition temperature was regulated to body temperature. The hydrogel can be degraded by extremely mild base of NaHCO3 based on phenolic ester bond.